PEMBELAJARAN MATEMATIKA DENGAN OPERATOR DASAR UNTUK ANAK SEKOLAH DASAR BERBASIS MOBILE - Dwija Wisnu Brata; Budi Santoso (Department of Science and Technology Ibrahimy University, 2016)
The concept of teaching mathematic is most important for educators by understanding and application of mathematics content that cater to students, especially primary school students. extending the interesting material, as well as providing assistance to the student to take assessment can assist in attraction, concentration and success in understanding mathematics. It is always related because not all students in a class is able to understand the material quickly, then the required factors that have an interest for children. The interesting will become the factors that support students in learning, if these factors can also be conceptualized as children's activities are carried out every day, it means that if the school use the curriculum, and the home environment playground are always supervised by the parent. so the Interesting in mathematics lessons can be realized also in the integration of emerging technologies, especially mobile phones. The majority the students today have the tool, it will be more efficient to develope of mathematical material is also contained in the mobile. The development can be implemented in mathematic education game. Games designed by researcher wishes to develop mobile based learning materials, especially in mathematic. the Experiments have performed in the implementation of mathematic games with basic operators to produce the final value of the overall respondents who rate amounted to 84.4%. it means that the level of engagement users, especially students very well in playing to respond the educational game designed.